Current Perspectives on Reducing the β-ODAP Content and Improving Potential Agronomic Traits in Grass Pea (Lathyrus sativus L.) - Das, Arpita; Parihar, Ashok K.; Barpete, Surendra; Kumar, Shiv; Gupta, Sanjeev (Frontiers in Plant Science, 2021)
Grass pea is well established as one of the most resilient and versatile crops that can thrive under extreme climatic circumstances such as cold, heat, drought, salt -affected soils, submergence and excessive rainfall along with resistance to several diseases and pests. However, despite the awareness of its virtues, its cultivation globally has decreased recently owing to the presence of a neurotoxin, β-N-oxalyl-L-α,β-diaminopropionic acid (β-ODAP) to cause neurolathyrism, a non-reversible neurological disorder in humans and animals. Significant repositories of Lathyrus germplasm are available across countries that have provided access to a wide range of agro-morphological traits as well as the low β ODAP content. Efforts have been made worldwide to use these germplasms for the genetic enhancement of grass pea to make this food safe for human consumption. Efforts on molecular breeding of this crop are also lagging. Molecular markers have also been used to evaluate the interspecific diversity as well as the phylogenetic relationship among the species and mapping studies. Transcriptomic studies have recently been undertaken on grass pea by deploying several second-generation sequencing techniques. In addition, a few studies have were attempted to unveil the genes and the underlying mechanism regulating the pathway of β-ODAP in grass pea. In grass pea, a metabolomics approach has been used to identify the metabolic processes associated with β-ODAP synthesis. Genome sequencing of grass pea is under way which is expected to be vital for whole -genome re-sequencing and gene annotation towards the identification of genes with novel functions. Recently, a draft genome sequence of grass pea was developed and some efforts are underway to resequence a diverse panel of grass pea comprising 384 germplasm lines. Owing to the scantiness of a successful transformation protocol, research on the application of modern approaches of genome editing viz., virus induced gene silencing, the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) or CRISPR-associated protein 9 (CRISPR/Cas9) system for the engineering of signalling pathways or regulatory mechanisms seeks immediate attention to reduc the β-ODAP content in seeds and to improve the potential agronomic traits in grass pea.